Designing the Networked Organization - Everett, Ken (Business Expert Press, 2011)
Ebook from IG Library ; Ken Everett proposes the network as the organization of the future, and he wrote this book, with the help of five colleagues, to help the architects of such future organizations. He started a network of necessity - limited financial resources - but then encountered surprising benefits. He discovered networked organizations to be resilient, innovative, and leader-full and that these characteristics arise out of the design. This potential, he says, applies equally to networks of independent associates as it does to traditional organizations willing to adopt a new style of leadership - a style closer to "hosting" than "commanding." This is a practice-based book: Its developmental model was earned through experience. The model lays out three phases: from connections to communities to coalitions, or from "doing fine" to "getting better" to "getting better at getting better." Ken Everett illustrates these claims with real-life examples. He describes how a family company with only 3 employees grew to be represented in 30 countries via 300 colleagues. The potential of the networked organization is new, and that's what this book is about.